58 An analysis of the quality of advanced care plan and DNACPR documentation prior to the introduction of the ReSPECT process. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Parmar, Kiran; Wilkinson, Emma; Henderson, Sinead; Smith, Clare
Abstract : An Advanced Care Plan (ACP) allows discussion and documentation of patient preferences for their future medical care which is not limited to resuscitation only. Despite national guidance, there remains poor communication and inconsistent documentation of ACP and DNACPR decisions, potentially resulting in inappropriate treatment and hospital admissions for patients. ReSPECT (Recommended Summary Plan for Emergency Care and Treatment) is a newly introduced emergency care plan which aims to help support advanced care discussions and record recommendations. We aimed to assess the quality of ACP and DNACPR documentation at a UK District General Hospital before introducing the ReSPECT form. Retrospective data was collected on all patients from two elderly care wards in March 2018 through case note review. Section headings on the ReSPECT form were used as the basis for collection. Data was also collected on ACP/DNAR decision communication on discharge documentation. 87 patients (52 male and 35 female). 25% (22) had ACP and 72% (63) had DNACPR agreed. Those with DNACPR, 79% (50) had discussion documented in clinical notes, and 57% (36) on discharge documentation. Those with ACP agreed, 68% (15) of discussions were documented in clinical notes, 95% (21) had ACP on discharge documentation completed by junior doctors. ACP and DNACPR decisions are individual to each patient and our initial data shows they are not always clearly documented. Interestingly, ACP decisions are found more on discharge summaries than recorded in medical notes. Discharge summaries are completed by junior doctors and therefore need support by clear senior decision making in the notes. This is currently missing for 27% of ACP decisions and highlights that discussions required for the ReSPECT process are not currently routinely documented. The ReSPECT form alongside web-based training was introduced in October 2018. The next step is to re-audit and assess its impact on documentation and communication.